Impact of stone density on outcomes in percutaneous nephrolithotomy (PCNL): an analysis of the clinical research office of the endourological society (CROES) pcnl global study database. (December 2013) - Anastasiadis, Anastasios; Onal, Bulent; Modi, Pranjal; Turna, Burak; Duvdevani, Mordechai; Timoney, Anthony; Wolf, J. Stuart; De La Rosette, Jean
Abstract Objective. This study aimed to explore the relationship between stone density and outcomes of percutaneous nephrolithotomy (PCNL) using the Clinical Research Office of the Endourological Society (CROES) PCNL Global Study database. Material and methods. Patients undergoing PCNL treatment were assigned to a low stone density [LSD, ≤ 1000 Hounsfield units (HU)] or high stone density (HSD, > 1000 HU) group based on the radiological density of the primary renal stone. Preoperative characteristics and outcomes were compared in the two groups. Results. Retreatment for residual stones was more frequent in the LSD group. The overall stone-free rate achieved was higher in the HSD group (79.3% vs 74.8%, p = 0.113). By univariate regression analysis, the probability of achieving a stone-free outcome peaked at approximately 1250 HU. Below or above this density resulted in lower treatment success, particularly at very low HU values. With increasing radiological stone density, operating time decreased to a minimum at approximately 1000 HU, then increased with further increase in stone density. Multivariate non-linear regression analysis showed a similar relationship between the probability of a stone-free outcome and stone density. Higher treatment success rates were found with low stone burden, pelvic stone location and use of pneumatic lithotripsy. Conclusions. Very low and high stone densities are associated with lower rates of treatment success and longer operating time in PCNL. Preoperative assessment of stone density may help in the selection of treatment modality for patients with renal stones.